Traffic Noise and its Impact on Wellness of the Residents in Sambalpur City – a Critical Analysis - SAHU, Alekh Kumar; NAYAK, Satish Kumar; MOHANTY, Chitta Ranjan; PRADHAN, Prasant Kumar (Archives of Acoustics, 2021)
Noise is unwanted sound judged to be unpleasant, loud or disruptive to hearing. Like air pollution, noise pollution is one of the serious matters of concern in urban areas. Noise pollution occurs when noise level exceeds certain limit and has deleterious effects on human health and wellness. The major sources of noise pollution are industries, road traffic, railways, airplane traffic and social celebrations. The traffic noise is notably high in cities due to higher density of population, frequent movement of people, good transport system coupled with increasing numbers of vehicles (on road). In this work, the assessments of traffic noise in Sambalpur city is presented. Twelve important locations were chosen for the assessment. Noise contours were drawn to visualize the spreading of traffic noise into its surroundings. At the same time, the effect of noise pollution on wellness of the exposed people was studied. The study shows that the traffic noise level and its effects, are both in an alarming stage in the city.